Characterization of Microwave Sintered Aluminium Composite Reinforced with Hydroxyapatite Extracted from Rihu Fish Scales - V.S.S. Venkatesh; Kalapala Prasad; Ashish B. Deoghare (Archives of Metallurgy and Materials, 2023)
In this study, Hydroxyapatite (HAp) is extracted from the Rihu fish scales which are generally dumped as garbage. The aluminium composite was fabricated through the powder metallurgy technique by reinforcing HAp (0, 5, 10 and 15 wt%) as a reinforcement. The fabricated samples were sintered through microwave sintering at 530℃ for 15 min under an argon gas environment. The fabricated composites were subjected to X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM) and Energy Dispersive Spectroscopy (EDS) analysis to confirm the constituting elements and to describe the reinforcement dispersion in the matrix. Uniform reinforcement dispersion was observed for the composite reinforces with 5%HAp, 10%HAp particles. The mechanical characterization results reveal that the Al-10% HAp composite exhibits a microhardness value of 123 ± 3 Hv and maximum ultimate tensile strength of 263 ± 10 MPa and 299 ± 9 MPa compression strength was obtained due to the presence of a strong bond among the aluminium and HAp particles.